Contingent Chaucer: experience, time, and modality in Chaucerian poetics - Buchanan, P (2021)
This thesis makes a new case for Chaucer as a philosophical poet, arguing that his art is profoundly entwined with the philosophy of contingency. Previous studies of contingency in Chaucer have interpreted the poet’s treatment of related issues (such as the mutability of language and the nature of free will) in relation to contemporaneous doctrinal controversies such as nominalism, voluntarism, and Lollardy. Going beyond these approaches, this thesis contends that Chaucer, synthesising a memorial omnium gatherum of philosophical learning, innovated a radical, anti-teleological poetics of contingency. Chaucerian contingency, the thesis states, is a comprehensive (yet by its nature fragmentary and modular) understanding of the relationship between individual lives and artistic creation under the conditions of phenomenal experience: the experience of time as linear, sequential and extensive; the translation of immediate consciousness into discrete concepts and words; the epistemological limits imposed by the temporality and multivocality of language. The thesis moves retrospectively through Chaucer’s career, first reassessing the Canon’s Yeoman’s Tale and Clerk’s Tale, before passing through Troilus and Criseyde and the House of Fame, revealing in each case how Chaucer reworks his sources to articulate his vision of contingency, and contest humanist narratives of utopian perfectibility and idealistic, teleological poetics. It situates each poem’s ideas of contingency in their fuller context within intellectual history, tracing the arc of Chaucer’s developing philosophical vision. In the process, it frees Chaucerian contingency from the strictures of nominalist analyses, using a new paradigm which asserts the basic homology and continuity of medieval and postmedieval thinking on the subject. Linking the conceptual affinities of Chaucer’s sources in the Neoplatonic, Augustinian, Boethian, Scotist and Thomist traditions with their counterparts in postmedieval contingency theory, it concludes that Chaucer was a critical node in a period-spanning tradition of literary explorations of contingency.